Real interest parity in the EU and the consequences for euro area membership: Panel data evidence, 1979 - 2005 - Martin O'Brien (The Economic and Social Research Institute (ESRI), 2007)
This paper examines whether macroeconomic convergence is an automatic outcome of forming a currency union by combining an analysis of real interest parity (RIP) in the EU with the argument for the endogeneity of the Optimum Currency Area (OCA) criteria. Using the DF-GLS and the CIPS* panel unit root test, RIP is tested for a sample of Euro area and non-Euro area EU member states with respect to Germany for key sub-periods covering 1979 M3 - 2005 M12. RIP is not found to hold for most of the sample between 1979 M3 and 1998 M12. There is evidence in favour of RIP for most of the Euro area sample during the 1999 M1 - 2005 M12 sub-period, exceptions being Ireland, Italy and Spain. RIP does not hold for any of the non-Euro area countries during the same period. This indicates some support for the endogeneity hypothesis, with the caveat that certain country-specific issues can seriously hinder the 'automatic' integration process.
Keywords: F33; F36; F40; 330; Real interest parity; OCA Criteria; European Monetary Union; Unit root tests; Entwicklungskonvergenz; Optimaler Währungsraum; Europäische Wirtschafts- und Währungsunion; Realzins; Panel; Unit Root Test; Schätzung; Deutschland; EU-Staaten